Intermodel spread of East Asian summer monsoon simulations in CMIP5. Issue 4 (19th February 2014) - Chen, Jinqiang; Bordoni, Simona
<x xml:space="preserve">Abstract</x> In this paper we diagnose the intermodel spread in the Coupled Model Intercomparison Project Phase 5 (CMIP5) East Asian summer monsoon (EASM) simulations in the context of the moist static energy and moisture budgets. We find that the spatial distribution of the EASM precipitation simulated by different models is highly correlated with the meridional stationary eddy velocity, defined as the deviation from the long‐term zonal mean. The correlation becomes more robust when energy fluxes into the atmospheric column are considered, consistent with recent observational analyses. The spread in the area‐averaged rainfall amount can be partially explained by the spread in the simulated globally averaged precipitation, with the rest primarily due to the lower level meridional wind convergence. Clear relationships between precipitation and zonal and meridional eddy velocities are observed.